Pengaruh Ukuran Perusahaan, Good Corporate Governace (GCG), dan Kualitas Audit terhadap Audit Delay - Muhammad Iqbal Saputra; Henri Agustin (Universitas Negeri Padang, 2021)
This study aims to determine the effect of firm size, good corporate governance as measured by the board of commissioners, the number of audit committees, audit committee meetings, and managerial ownership and audit quality on audit delay. This research was conducted on industrial sector companies that produce raw materials listed on the Indonesian stock exchange in 2016-2019. The data in this study were obtained from the annual reports of each company. The population in this study is the raw material industry using a sampling technique, namely purposive sampling. The sample in this study amounted to 52 companies for a 4 year period. Analysis of the data used is multiple regression analysis. The results of this study explain that: Company size has a negative and insignificant effect, Board of Commissioners has a negative and insignificant effect, Number of Audit Committees has a negative and insignificant effect, Audit Committee Meetings have a significant negative effect, Managerial Ownership has a negative and significant effect, and Audit Quality has a negative effect. and significant to audit delay.